Answer

Verified

397.5k+ views

**Hint:**Here, we will use the rectangular coordinates and simplify it to find the value of \[{r^2}\]. Then we will rewrite the given equation and substitute the obtained value and rectangular coordinate to simplify it further. Then by using the trigonometric identity and exponent rules we will convert the equation into the rectangular form.

**Formula Used:**

We will use the following formula:

1. The square of the sum of the numbers is given by \[{\left( {a + b} \right)^2} = {a^2} + {b^2} + 2ab\].

2. Product rule of exponents:\[{a^m} \times {a^n} = {a^{m + n}}\]

3. Power rule for Exponents: \[{\left( {{a^m}} \right)^n} = {a^{mn}}\]

**Complete Step by Step Solution:**

We are given the equation in a Polar form \[{r^2} = \sin \theta \].

Now, multiplying both the sides of the equation with \[r\], we get

\[ \Rightarrow {r^2} \cdot r = r \cdot \sin \theta \] ……………………………………………….\[\left( 1 \right)\]

We know that in Rectangular form \[x = r\cos \theta \] and \[y = r\sin \theta \].

Now squaring and adding the coordinates of the Rectangular form, we get

\[{x^2} + {y^2} = {r^2}{\cos ^2}\theta + {r^2}{\sin ^2}\theta \]

By taking out the common factor, we get

\[ \Rightarrow {x^2} + {y^2} = {r^2}\left( {{{\cos }^2}\theta + {{\sin }^2}\theta } \right)\]

Now, by using the Trigonometric Identity \[{\cos ^2}\theta + {\sin ^2}\theta = 1\], we get

\[ \Rightarrow {x^2} + {y^2} = {r^2}\left( 1 \right)\]

\[ \Rightarrow {x^2} + {y^2} = {r^2}\] ……………………………………………\[\left( 2 \right)\]

By substituting above equation in equation \[\left( 1 \right)\], we get

\[\left( {{x^2} + {y^2}} \right) \cdot r = y\]

Dividing both sides by \[r\], we get

\[ \Rightarrow \left( {{x^2} + {y^2}} \right) = \dfrac{y}{r}\]…………………………………….\[\left( 3 \right)\]

Taking square root on both the sides of the equation \[\left( 2 \right)\], we get

\[r = \pm \sqrt {{x^2} + {y^2}} \]

Substituting the value of \[r\] in the equation \[\left( 3 \right)\], we get

\[\left( {{x^2} + {y^2}} \right) = \dfrac{y}{{ \pm \sqrt {{x^2} + {y^2}} }}\]

Now, by squaring on both the sides, we get

\[ \Rightarrow {\left( {{x^2} + {y^2}} \right)^2} = \dfrac{{{y^2}}}{{{x^2} + {y^2}}}\]

Now, by using the algebraic identity \[{\left( {a + b} \right)^2} = {a^2} + {b^2} + 2ab\], we get

\[ \Rightarrow {\left( {{x^2}} \right)^2} + {\left( {{y^2}} \right)^2} + 2\left( {{x^2}} \right)\left( {{y^2}} \right) = \dfrac{{{y^2}}}{{{x^2} + {y^2}}}\]

Using the Power rule for exponents \[{\left( {{a^m}} \right)^n} = {a^{mn}}\], we get

\[ \Rightarrow \left( {{x^4}} \right) + \left( {{y^4}} \right) + 2\left( {{x^2}} \right)\left( {{y^2}} \right) = \dfrac{{{y^2}}}{{{x^2} + {y^2}}}\]

Multiplying \[{x^2} + {y^2}\] on both the sides, we get

\[ \Rightarrow \left[ {\left( {{x^4}} \right) + \left( {{y^4}} \right) + 2\left( {{x^2}} \right)\left( {{y^2}} \right)} \right]\left( {{x^2} + {y^2}} \right) = {y^2}\]

Now, by using the FOIL method, we get

\[ \Rightarrow {x^2}\left( {\left( {{x^4}} \right) + \left( {{y^4}} \right) + 2\left( {{x^2}} \right)\left( {{y^2}} \right)} \right) + {y^2}\left( {\left( {{x^4}} \right) + \left( {{y^4}} \right) + 2\left( {{x^2}} \right)\left( {{y^2}} \right)} \right) = {y^2}\]

Simplifying the equation, we get

\[ \Rightarrow \left( {\left( {{x^2} \cdot {x^4}} \right) + \left( {{x^2} \cdot {y^4}} \right) + 2\left( {{x^2} \cdot {x^2}} \right)\left( {{y^2}} \right)} \right) + \left( {\left( {{y^2} \cdot {x^4}} \right) + \left( {{y^2} \cdot {y^4}} \right) + 2\left( {{x^2}} \right)\left( {{y^2} \cdot {y^2}} \right)} \right) = {y^2}\]

Now, by using product rule of exponents \[{a^m} \times {a^n} = {a^{m + n}}\], we get

\[ \Rightarrow \left( {\left( {{x^6}} \right) + \left( {{x^2}{y^4}} \right) + 2\left( {{x^4}} \right)\left( {{y^2}} \right)} \right) + \left( {\left( {{y^2}{x^4}} \right) + \left( {{y^6}} \right) + 2\left( {{x^2}} \right)\left( {{y^4}} \right)} \right) = {y^2}\]

Rewriting the equation, we get

\[ \Rightarrow {y^2} = {x^6} + {x^2}{y^4} + 2{x^4}{y^2} + {y^2}{x^4} + {y^6} + 2{x^2}{y^4}\]

Adding the like terms, we get

\[ \Rightarrow {y^2} = {x^6} + 3{x^2}{y^4} + 3{x^4}{y^2} + {y^6}\]

**Therefore, the rectangular form of \[{r^2} = \sin \theta \] is \[{y^2} = {x^6} + 3{x^2}{y^4} + 3{x^4}{y^2} + {y^6}\].**

**Note:**

We know that Polar coordinates are used to specify only two dimensions whereas Rectangular Coordinates which is also called as Cartesian Coordinates is used to specify three dimensions in a plane. FOIL method is a method of multiplying the binomials by multiplying the first terms, then the outer terms, then the inner terms and at last the last terms. Using this we can easily combine like terms.

Recently Updated Pages

Mark and label the given geoinformation on the outline class 11 social science CBSE

When people say No pun intended what does that mea class 8 english CBSE

Name the states which share their boundary with Indias class 9 social science CBSE

Give an account of the Northern Plains of India class 9 social science CBSE

Change the following sentences into negative and interrogative class 10 english CBSE

Advantages and disadvantages of science

Trending doubts

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

Which are the Top 10 Largest Countries of the World?

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

Differentiate between homogeneous and heterogeneous class 12 chemistry CBSE

Difference Between Plant Cell and Animal Cell

10 examples of evaporation in daily life with explanations

Give 10 examples for herbs , shrubs , climbers , creepers

Write a letter to the principal requesting him to grant class 10 english CBSE

How do you graph the function fx 4x class 9 maths CBSE